2009
DOI: 10.1097/aud.0b013e3181aec5bc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Audibility and Multichannel Wide Dynamic Range Compression on Consonant Recognition for Listeners with Severe Hearing Loss

Abstract: Objective-This study examined the effects of multichannel wide-dynamic range compression (WDRC) amplification and stimulus audibility on consonant recognition and error patterns.Design-Listeners had either severe or mild-to-moderate sensorineural hearing loss. Each listener was monaurally fit with a wearable hearing aid using typical clinical procedures, frequency-gain parameters and a hybrid of clinically prescribed compression ratios for DSL (Scollie et al., 2005) and NAL-NL (Dillon, 1999). Consonant-vowel n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…Consistent with all of these effects, an analysis of speech and masker levels using the phase inversion technique indicated that while overall speech levels were higher for conditions with short RT and more channels, so were overall masker levels, for a net decrease in long-term output SNR. Therefore, audibility of certain speech cues for some listeners likely came at the perceptual cost of a more degraded signal (Souza & Turner, 1998, 1999; Davies-Venn et al ., 2009; Kates, 2010). …”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with all of these effects, an analysis of speech and masker levels using the phase inversion technique indicated that while overall speech levels were higher for conditions with short RT and more channels, so were overall masker levels, for a net decrease in long-term output SNR. Therefore, audibility of certain speech cues for some listeners likely came at the perceptual cost of a more degraded signal (Souza & Turner, 1998, 1999; Davies-Venn et al ., 2009; Kates, 2010). …”
Section: Discusssionmentioning
confidence: 99%
“…First, as presentation level changes, the relative importance of factors related to audibility and envelope distortion may change (Davies-Venn et al ., 2009; Kates, 2010). At low presentation levels, parameters that promote audibility, namely short RT and many channels, may lead to more favorable speech recognition.…”
Section: Discusssionmentioning
confidence: 99%
“…For low-level speech, compression amplification improves audibility, and this improvement in audibility also results in an improvement in speech recognition (e.g., Davies-Venn et al, 2007; 2009; Kates, 2010; Kuk, 2000; Souza, 2002). Less information is available regarding the benefits conferred by improved audibility at conversational and higher speech levels (Kates, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that listeners with hearing loss will be forced to shift reliance to temporal cues has been put forth in several papers (Boothroyd, Springer, Smith, & Schulman, 1988; Christensen & Humes, 1997; Davies-Venn & Souza, 2014; Davies-Venn, Souza, Brennan, & Stecker, 2009; Souza, Jenstad, & Folino, 2005). That hypothesis relies, in part, on the idea that temporal cues will be more resistant to degradation from hearing loss than spectral cues, provided the listener can access a sufficiently wide signal bandwidth.…”
mentioning
confidence: 99%